An investigation of control allocation methods for the ADMIRE simulation model - Gulcan, Nilsu; Kurt, Huseyin Burak; Karaman, Atakan; Millidere, Murat (American Institute of Aeronautics and Astronautics (AIAA), 2023)
This paper presents a comparative study of various control allocation methods, using ADMIRE as a benchmark simulation model. The Ganged Pseudo-Inverse, Weighted Pseudo-Inverse, Cascaded Generalized-Inverse, Daisy Chain, and Linear Programming approaches are evaluated and compared against each other using open loop and closed loop analysis with Euclidean-Norm. In open-loop analysis, control allocation methods are analyzed for each approach that can produce an admissible solution and be able to attain commanded moments. Then, in closed-loop analysis, control allocation methods are compared using ADMIRE nonlinear simulation model for predefined maneuvers which are defined by multiple points in the flight envelope.